MITOLOGI SEBAGAI PENDIDIKAN KEBENCANAAN DALAM MEMAHAMI ERUPSI GUNUNG MERAPI - Permana, S.Pd., M.Pd., Dr. Septian Aji; Hartanto, Supri (Universitas Muria Kudus, 2019)
This study aims to analyze community culture in understanding the eruption of Mount Merapi and analyze the meaning of education implied in the mythology of Mount Merapi. This study uses a qualitative approach. The informants in this study were the Cangkringan community, the caretaker of Mount Merapi, the NGO (Non-Governmental Organization) Cangkringan. Data collection techniques are carried out by participant observation and in-depth interviews. The collected data is then analyzed using domain, taxonomic, compound, and cultural theme analysis techniques.The findings in the form of public trust in Mount Merapi that people believe Mount Merapi is inhabited by supernatural beings who should have a life like humans. The supernatural beings have their own organization that regulates the government hierarchy with all its attributes and activities. One form of government hierarchy of supernatural beings that is closely related to society is that people believe that Mount Merapi is a Palace of Fine Beings.